Ð‘ÐµÐ·Ð¾Ñ‚Ð¼Ñ‹Ð²Ð¾Ñ‡Ð½Ñ‹Ð¹ Ð¼ÐµÑ‚Ð¾Ð´ ÐºÑ€Ð¸Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð¸Ñ ÐºÐ¾Ñ€Ð´Ð¾Ð²Ð¾Ð¹ ÐºÑ€Ð¾Ð²Ð¸: Ð¾Ñ†ÐµÐ½ÐºÐ° Ð¿Ð¾Ð¿ÑƒÐ»ÑÑ†Ð¸Ð¾Ð½Ð½Ð¾Ð³Ð¾ ÑÐ¾ÑÑ‚Ð°Ð²Ð° ÑÐ´Ñ€Ð¾ÑÐ¾Ð´ÐµÑ€Ð¶Ð°Ñ‰Ð¸Ñ… ÐºÐ»ÐµÑ‚Ð¾Ðº - Babiychuk, L. A.; Zubov, P. M.; Ryazantsev, V. V.; Zubova, O. L. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2008)
There were elaborated new effective methods for isolation and cryopreservation of cord blood nucleated cells, which allow to preserve quite whole quantitative and qualitative contents of nucleated cells (including hemopoietic cells) after isolation and demonstrate quite a high recovery after freeze-thawing. The analysis of CD45+-cell population content testified that CD34+-cells as well as lymphocytes and monocytes manifested a high level of recovery and viability after freezing.